2007
DOI: 10.1080/10611860701453836
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial efficacy of amphotericin B bearing emulsomes against experimental visceral leishmaniasis

Abstract: Amphotericin B (AmB) was formulated in trilaurin-based emulsomes (nanosize lipid particles) stabilized by soya phosphatidylcholine (PC), as a new delivery system for macrophage targeting for the treatment of visceral leishmaniasis (VL). Emulsomes were modified by coating them with macrophage-specific ligand (O-palmitoyl mannan, OPM). The antileishmanial activity of AmB-deoxycholate (AmB-Doc) and emulsome entrapped AmB was tested in vitro in Leishmania donovani infected macrophage-amastigote system (J774A.1 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 42 publications
0
26
0
2
Order By: Relevance
“…After washing, cells were fixed in 10% formalin in PBS and observed by CLSM (Olympus IX 81, Center Valley, PA, USA) equipped with a × 60 oil objective lens. Percent parasite inhibition in treated wells was calculated using the following formula reported and published by our associated group previously (2,6).…”
Section: Ex-vivo Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…After washing, cells were fixed in 10% formalin in PBS and observed by CLSM (Olympus IX 81, Center Valley, PA, USA) equipped with a × 60 oil objective lens. Percent parasite inhibition in treated wells was calculated using the following formula reported and published by our associated group previously (2,6).…”
Section: Ex-vivo Stabilitymentioning
confidence: 99%
“…Studies on VL revealed that organs such as spleen and liver serve as safe havens for parasites residing inside the macrophages. Most of the antileishmanial drugs presently in use, fail to penetrate macrophages within which parasite creep and that derives researchers to pursue delivery systems and their engineered versions in order to be therapeutically effective (2). Currently surviving therapies for leishmaniasis are very toxic and also started exhibiting emergence of drug-resistant parasitic strains.…”
Section: Introductionmentioning
confidence: 99%
“…The Ex-vivo studies were performed by observing drug leaching and change in particle size following incubation of PCL-NPs with freshly pooled rat serum at 37 ± 1 0 C. The drug content of the PCL-NPs was determined by the method described previously with slight modifications (16). PCL-NPs formulations (1 mL) were incubated with 2 ml serum at 37 ± 1°C for 1, 2, 4, 6 and 24 hrs.…”
Section: Ex-vivo Stabilitymentioning
confidence: 99%
“…(2, 3, 4, 5 mg for AmB and 5, 10, 15, and 20 mg for DOX) in different formulations (Table 1) for determining optimum AmB and DOX content (15). Average particle size of different formulations was determined by particle size analyzer (Delsa Nano C, Beckman Coulter, USA) and percent drug entrapment in different formulations was also determined as described previously (16). PCL-NPs with optimum AmB and DOX to polymer content were optimized for optimum sonication time in terms of average particle size.…”
Section: Optimization Of Pcl-nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation